A Book Review LITERARY WORKS IN ENGLISH LEARNING AS SHOWN IN DISCOVERING FICTION - Antonius Herujiyanto (Soegijapranata Catholic University, 2008)
Discovering Fiction is a two-level anthology of American short stories by classic and contemporary American authors, released on May 28, 2005. The authors, Judith Kay and Rosemary Gelshenen, have definitely worked hard in collecting the short stories and organized them into five thematic sections with two up to four units and a section review.